Multi-scale modelling approach for the pushover analysis of existing RC shear walls?Part II Experimental verification. - Mulas, Maria Gabriella (Earthquake engineering & structural dynamics.)
In a companion paper two different modelling approaches have been described, operating at the meso-scale of the fibre elements and at the micro-scale of the finite element (FE) method. The aim of this paper is to explore the efficiency of these models in the pushover analysis for the seismic assessment of existing reinforced concrete (RC) structures. To this purpose a prototype reference structure, one of the RC shear walls designed according to the multi-fuse concept and tested on shaking table for the CAMUS Project, is modelled at different levels of refinement. At the micro-scale the reinforcement and anchorage details are described with increasing accuracy in separate models, whereas at the meso-scale one single model is used, where each element represents a large part of the structure. Static incremental non-linear analyses are performed with both models to derive a capacity curve enveloping the experimental results and to reproduce the damage pattern at the displacement level where failure is reached. The comparison between experimental and numerical results points out the strong and weak points of the different models inside the procedure adopted, and the utility of an integration of results from both approaches. This study confirms, even for the rather difficult case at study, the capability of the pushover in reproducing the non-linear dynamic response, both at a global and a local level, and opens the way to the use of the models within a displacement-based design and assessment procedure.